2017
DOI: 10.1002/mnfr.201601010
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean tomato-based sofrito protects against vascular alterations in obese Zucker rats by preserving NO bioavailability

Abstract: This is the first evidence of tomato-based sofrito protection against vascular alterations that could precede major cardiometabolic complications in obesity. These results contribute to explain the therapeutic properties of the Mediterranean diet in obesity-related disorders. Therefore, sofrito is an attractive dietary approach against vascular alterations in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Taking into account sofrito ’s rich bioactive compound content, here we analyzed the impact of a regular consumption of sofrito on insulin sensitivity in an obese rat model and identified FGF21 signaling as a mechanism by which sofrito could exert, at least in part, its healthy effects. This work is closely related to a previous one where the authors described that sofrito protects against vascular alterations that could precede major cardiometabolic complications in obesity …”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Taking into account sofrito ’s rich bioactive compound content, here we analyzed the impact of a regular consumption of sofrito on insulin sensitivity in an obese rat model and identified FGF21 signaling as a mechanism by which sofrito could exert, at least in part, its healthy effects. This work is closely related to a previous one where the authors described that sofrito protects against vascular alterations that could precede major cardiometabolic complications in obesity …”
Section: Introductionsupporting
confidence: 69%
“…Obesity is usually associated with insulin resistance and glucose intolerance. OZR showed increased levels of blood glucose and those values are not significantly changed by a CD supplemented with sofrito . To test the effect of sofrito on insulin sensitivity we performed an ITT with the different experimental groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have shown that the consumption of processed tomato‐based products has a greater correlation with a low incidence of chronic‐degenerative diseases compared to raw tomato . Moreover, tomato sofrito consumption is associated with improved cardiovascular risk parameters and insulin sensitivity, and activates thermogenesis by browning fat tissue . This key component of the Mediterranean diet has also recently been correlated with the manifestation of less aggressive prostate cancer …”
Section: Introductionmentioning
confidence: 99%
“…10 Moreover, tomato sofrito consumption is associated with improved cardiovascular risk parameters and insulin sensitivity, and activates thermogenesis by browning fat tissue. 11,12 This key component of the Mediterranean diet has also recently been correlated with the manifestation of less aggressive prostate cancer. 13 The aim of this study was to evaluate how the sofrito cooking technique and ingredients used to prepare tomato sofrito sauce could improve the content of tomato phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%